THE IMPORTANCE OF AMBULANCE IN DROWNING CASES - Gafurov Abduvoid Khuseinovich; Azimov Ilyosbek Qahramon o’g’li; Egamberdiyev Jasurbek Jumanazar o’g’li; Nurmatov Nurmuhammad Jamoliddin o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides feedback on first aid measures considered by the teacher.